Cromoglycate and nedocromil enhanced the reactive oxygen species-dependent suppressions with, but not without, dexamethasone in ischaemic and histamine paw oedema of mice - Y. Oyanagui (Mediators of Inflammation)
Anti-inflammatory actions of two anti-allergic drugs, alone or with dexamethasone (Dex) were examined in two models, because inflammation is claimed to be important for allergic events, especially for asthma. Cromoglycate and nedocromil were tested in ischaemic- and histamineinduced paw oedema models of mice. These antiallergic drugs (1–100 mg/kg, i.p.) failed to suppress these oedemata, but enhanced the suppressions by a low dose of dexamethasone (0.1 mg/kg, s.c.) at 3–8 h after Dex injection. The mode of effects by anti-allergic drugs resembled that of a natural antioxidant (α-tocopherol, β-carotene etc.), and was different from that of an immunosuppressant like FK506. The enhancing potencies of the two anti-allergic drugs were similar at 6 h after Dex in both oedemata, and were diminished by superoxide dismutase (SOD) or catalase (i.p.). Cycloheximide completely abolished suppressions. Nedocromil, but not cromoglycate, inhibits inflammatory events. Therefore, there are common unknown actions by which the two anti-allergics enhance suppression by Dex. A possible mechanism of this action was supposed to enhance the superoxide and/or hydrogen peroxide-dependent glucocorticoid receptor (GR) signalling in the target cells.